Pengembangan Alat Peraga Fisika Sederhana Berbahan Bekas Pakai pada Materi Gerak Lurus - Fartina Fartina; Tsamarul Hizbi; Laxmi Zahara; Mudrikah Mudrikah (Kappa Journal, 2022)
This research is aim to develop or to make a physics tool model with simple used materials for straight motion learning. This research is development research. The Method in this resenta depelovment is ADDIE, which means Analysis, Design, Development and Implementation. To test this product development, the resentati make validation through material expert, media expert, teacher questionnaire response subject matter, and students response questionnaire and worksheet learning resentatio test. The technique of data collection usesquestionnaire and test. The data analysis of distribute resentation is done by data tabulation from each validator, resulted anresent score and compare with 5 scale. Based on the measurement from three media expert shows that the tool model include suitable category with a value resentation are 88%. While, based on the assessment from three material expert shows that the quality of the tool model with suitable category of resentation value are 89,34%. Based on three teachers subject learning show that the quality of the tool model including very suitable category of resentation value are 93%. While, the assessment from the students including very good suitable category score are 88,3%. The data result from students learning used this tool model get the value 80 which is above the KKM. It can be shows that the pyshics tool model with simple used material is effective in learning process at MAS NW Kalijaga